2011
DOI: 10.1111/j.1479-8425.2011.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dream anxiety and subjective sleep quality between chronotypes

Abstract: Morning and evening-type individuals differ on a number of psychological and biological variables. In this study, we aimed to investigate the relationship between sleep quality, dream anxiety, and chronotypes. A sample of 264 university students, aged between 17 and 26 years, completed the Morningness-Eveningness Questionnaire, the Pittsburgh Sleep Quality Index, and the Van Dream Anxiety Scale for assessing nightmare frequency and the dream anxiety caused by frightening dreams. Main findings indicated that ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 52 publications
8
38
1
1
Order By: Relevance
“…For this reason, this stage of life means both developmental and social changes which may be stressful to most of students. Evening types suffer from higher levels of anxiety, obsessive-compulsiveness, hostility and phobia symptoms (Vardar, Vardar, Molla, Kaynak & Ersoz, 2008) and usually have nightmares and suffer from dream anxiety (Selvi et al, 2012). Linked to physical, psychological and social changes, evening type adolescents are forced to adapt their biological preferences to the early school schedules, consequently, morningness-eveningness may be a risk factor to consider concerning health and anxiety symptoms during this stage of life.…”
Section: Morningness-eveningness and Healthmentioning
confidence: 99%
“…For this reason, this stage of life means both developmental and social changes which may be stressful to most of students. Evening types suffer from higher levels of anxiety, obsessive-compulsiveness, hostility and phobia symptoms (Vardar, Vardar, Molla, Kaynak & Ersoz, 2008) and usually have nightmares and suffer from dream anxiety (Selvi et al, 2012). Linked to physical, psychological and social changes, evening type adolescents are forced to adapt their biological preferences to the early school schedules, consequently, morningness-eveningness may be a risk factor to consider concerning health and anxiety symptoms during this stage of life.…”
Section: Morningness-eveningness and Healthmentioning
confidence: 99%
“…Circadian dysregulation between individual chronotype and daily activity are known to cause http://dx.doi.org/10.1016/j.eplepsyres.2015.11.010 0920-1211/© 2015 Published by Elsevier B.V. sleep problems. One study showed that individuals with a circadian preference for evening activities (evening-type) showed higher prevalence of sleep disturbance than morningness or intermediated-type (Selvi et al, 2012). Homeostatic changes in sleep deprivation, as well as different individual chronotype can cause sleep disorders.…”
Section: Introductionmentioning
confidence: 97%
“…Recent evidence also links eveningness to more frequent and intense nightmares (Nielsen, 2010; Selvi et al, 2012). This link suggests that the affective dysregulation, which characterizes evening-types' waking state, may also extend to the rapid-eye movement (REM) sleep state during which nightmares primarily occur.…”
Section: Introductionmentioning
confidence: 99%